Knowledge and Compliance with the Infection Control Protocol in Dentistry at a Costa Rican University - Dittel-Jiménez, Carmen (2025)
Biosafety is essential for reducing exposure to infections and preventing contamination in dental practices. This study aimed to assess the knowledge level and compliance with the infection control protocol at a dental school within a university in Costa Rica. An online survey was distributed to all students, faculty, and support staff working in the university’s dental clinics between May and June 2022. The questionnaire included items on sociodemographic characteristics, training and mechanisms of information dissemination, access to personal protective equipment (PPE), perceptions of protocol adherence, sharps injuries, and vaccination practices. Descriptive statistics and chi-square tests were used to analyze the data. A total of 232 individuals participated; the majority were women (71%). Clinical students represented 35% of respondents, followed by faculty (30%), preclinical students (25%), and support staff (10%). While 98% reported being familiar with the protocol and 79% had received training, the proportion of trained faculty was notably lower (55%). Faculty also reported lower adherence to PPE use and biomedical waste management procedures. Preclinical students reported limited access to handwashing stations and related supplies. Only 66% of participants reported performing proper hand hygiene, and 70% cleaned electronic equipment appropriately. Vaccination rates for hepatitis B and COVID-19 were high, but antibody testing frequency was low. Despite widespread awareness of infection control protocols, adherence varies across groups. Faculty and preclinical students exhibit greater challenges in compliance. Strengthening training efforts and improving access to essential biosafety resources are critical to enhancing protocol implementation and ensuring safer clinical environments.